Fondasi Utama dalam Menjaga Konsistensi Kualitas Layanan Beauty Salon - Bunga Julian Sunaryo; Nabila Amalia; Nevita Sherly Tri Hapsari; Shalasha Haura Aqilah Sa’adah; Sri Endah Wahyuningsih (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Service quality is a strategic factor that plays a crucial role in increasing competitiveness and supporting business sustainability in the beauty services sector. This study aims to analyze the factors influencing service quality at SYR Beauty Salon, UNNES Branch. The study employed a descriptive qualitative approach, with data collection techniques consisting of observations and interviews with informants involved in the service process. The data obtained were analyzed descriptively to identify various aspects contributing to salon service quality. The results indicate that service quality is influenced by several key factors: employee competence and cooperation, the implementation of Standard Operating Procedures (SOPs), the quality of products used in the service, the effectiveness of communication with customers, and the accuracy of hair condition diagnosis prior to treatment. The use of social media also plays a role in supporting the delivery of information, communication, and service promotion to customers. The research findings indicate that optimal service quality can be achieved through competent and professional human resource management, the implementation of standardized work systems, and a service orientation focused on customer needs and expectations. These factors contribute to consistent service quality, increased customer satisfaction, and strengthened the competitiveness of beauty services businesses.